Discovery of Dense Ferromanganese Nodules in the Central Basin of the South China Sea: Insights Into Metallogenesis Processes and Resource Potential - Jiangbo Ren; Yong Yang; Lixue Zhang; Limin Zhang; Yinan Deng; Yingzhi Ren; Shuang Hong; Jinfeng Ma; Xianze Deng; Miao Yu; Zhen Sun; Gaowen He (Geophysical Research Letters)
Abstract Ferromanganese deposits in the South China Sea (SCS) hold significant strategic metal resources, yet their distribution remains poorly understood. To address this gap, we conducted an integrated study across 6,600 km2 in the central basin of the SCS, combining sampling, seafloor video, and multi‐beam backscatter acoustic surveys. A high‐backscatter zone of 1.21 km2 on the Jiaolong seamount was identified as a ferromanganese nodule‐rich area, contrasting with the abyssal basin. The ferromanganese nodules exhibit high vernadite contents and atypical hydrogenesis characteristics, including high Fe/Mn and Fe/Co ratios, and elevated Pb and rare earth element contents. These features suggest that marginal seas are more effective in supplying short‐life cycle elements. Seamounts in the central basin may enhance circulation efficiency, facilitating sediment removal and dissolved oxygen recharge, thereby promoting ferromanganese deposit formation in certain areas. This study contributes to the further exploration of ferromanganese deposits in the SCS.